Inter-charity competition under spatial differentiation: Sorting, crowding, and spillovers - Carlo Gallier; Timo Goeschl; Martin Kesternich; Johannes Lohse; Christiane Reif; Daniel Römer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
We study spatially differentiated competition between charities by partnering with two foodbanks in two neighboring cities to conduct a field experiment with roughly 350 donation appeals. We induce spatial differentiation by varying the observability of charities' location such that each donor faces a socially close 'home' and a distant 'away' charity. We find that spatially differentiated competition is characterized by sorting, crowding-in, and an absence of spillovers: Donors sort themselves by distance; fundraising (through matching) for one charity raises checkbook giving to that charity, irrespective of distance; but checkbook giving to the unmatched charity is not affected. For lead donors, this implies that the social distance between donors and charities is of limited strategic important. For spatially differentiated charities, matching 'home' donations maximizes overall charitable income. Across both charities, however, the additional funds raised fail to cover the cost of the match, despite harnessing social identity for giving.
Keywords: C9; D7; H4; 330; altruism; public goods; charitable giving; social distance; field experiment; competition